Brain Microstructural Changes and Cognitive Function in Non-Demented Essential Tremor Patients: A Diffusion Tensor Imaging Study. - Sengul, Y; Otcu, H; Corakcı, Z; ÇORAKÇI, ZEYNEP; Sengul, HS; Dowd, H; Ustun, I; Alkan, ALPAY; ALKAN, ALPAY; Louis, ED (My University, 2020)
Background Essential tremor (ET) is disease with both motor and non-motor features. Notable among the non-motor features is cognitive impairment. While this impairment has been attributed to cortico-thalamo-cerebellar pathway pathology, it is likely that a more complicated involvement of brain structures underlies cognitive function in ET. Objective To evaluate the brain microstructural changes of both white matter and grey matter in ET using region of interest based diffusion tensor imaging (DTI), and to correlate these changes with cognitive function assessed during detailed neuropsychological testing. Method Thirty-five non-demented ET patients with a range of cognitive function (Clinical Dementia Rating = 0-0.5, mean age = 57.5 +/- 16.7 years, age range = 23-76 years) underwent a comprehensive neuropsychological evaluation and brain magnetic resonance imaging, including DTI. DTI findings were reported as fractional anisotropy, average diffusion coefficient, these values were evaluated for 32 ROIs. Cognitive domains included attention, visuospatial functions, executive function, verbal memory, visual memory, and language. Domain Z-scores were calculated each cognitive domain and compared for each brain region. Results Microstructural changes in prefrontal cortical areas (dorsolateral, ventrolateral), paralimbic and limbic structures (posterior cingulate cortex, precuneus, hippocampus), basal ganglia (substantia nigra, putamen, caudate nucleus) and white matter bundles (corpus callosum, anterior thalamic radiation, longitudinal fasciculus, frontooccipital fasciculus, etc.) correlated with specific domains of cognitive function in ET patients. Conclusion These data suggest that not only the cerebello thalamocortical pathway, but numerous other brain structures are related to level of cognitive performance and possibly underlie cognitive dysfunction in ET.